Complete mitochondrial genome sequence of the Himalayan Griffon, Gyps himalayensis (Accipitriformes: Accipitridae): Sequence, structure, and phylogenetic analyses. Issue 15 (9th July 2019) - Jiang, Lichun; Peng, Liqing; Tang, Min; You, Zhangqiang; Zhang, Min; West, Andrea; Ruan, Qiping; Chen, Wei; Merilä, Juha
Abstract: This is the first study to describe the mitochondrial genome of the Himalayan Griffon, Gyps himalayensis, which is an Old World vulture belonging to the family Accipitridae and occurring along the Himalayas and the adjoining Tibetan Plateau. Its mitogenome is a closed circular molecule 17, 381 bp in size containing 13 protein‐coding genes, 22 tRNA coding genes, two rRNA‐coding genes, a control region (CR), and an extra pseudo‐control region (CCR) that are conserved in most Accipitridae mitogenomes. The overall base composition of the G. himalayensis mitogenome is 24.55% A, 29.49% T, 31.59% C, and 14.37% G, which is typical for bird mitochondrial genomes. The alignment of the Accipitridae species control regions showed high levels of genetic variation and abundant AT content. At the 5′ end of the domain I region, a long continuous poly‐C sequence was found. Two tandem repeats were found in the pseudo‐control regions. Phylogenetic analysis with Bayesian inference and maximum likelihood based on 13 protein‐coding genes indicated that the relationships at the family level were (Falconidae + (Cathartidae + (Sagittariidae + (Accipitridae + Pandionidae))). In the Accipitridae clade, G. himalayensis is more closely related to Aegypius monachus than to Spilornis cheela . The complete mitogenome of G. himalayensis provides a potentially useful resource for further exploration of the taxonomic status and phylogenetic history of Gyps species. Abstract : This is the first study to describe the mitochondrial genome of the Himalayan Griffon, Gyps himalayensis, which is an Old World vulture belonging to the family Accipitridae and occurring along the Himalayas and the adjoining Tibetan Plateau. The overall base composition of the G. himalayensis mitogenome is 24.55% A, 29.49% T, 31.59% C, and 14.37% G, which is typical for bird mitochondrial genomes. At the 5′ end of the domain I region, a long continuous poly‐C sequence was found. Two tandem repeats were found in the pseudo‐control regions. Phylogenetic analysis indicated that G. himalayensis is more closely related to A. monachus than to S. cheela . The complete mitogenome of G. himalayensis provides a potentially useful resource for further exploration of the taxonomic status and phylogenetic history of Gyps species.